THE ROLE OF DIGITAL MARKETING TRANSFORMATION IN ACHIEVING COMPETITIVE ADVANTAGE FOR THE EDUCATIONAL INSTITUTION: AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF FACULTY MEMBERS AT AL-NOUR UNIVERSITY - Jarjees Omair Abbas; Sara Azzam Saadi Hassan (Jurnal Ekonomi, Bisnis dan Pendidikan, 2026)
The research aims to determine the role of digital transformation in marketing in regarding to attaining the competitive edge for the educational institution. This research was carried out at Al-Nour University. At the current pace of technological advancements, it is required that the education sector, especially Al-Noor University, keeps up with technological and digital advancements along with utilizing them in its scientific, administrative, and technical functions in order to attain competitive advantage. To achieve the goals of the study, the analytical method was employed to obtain findings and relied on data sources, by circulating questionnaires, which included sample of (100) members of Al-Noor University. The analysis was done by the researchers based on statistical analysis program (SPSS v25) and (Smart PLS) program. Results indicated that there has been a highly meaningful positive connection and impact of digital marketing transformation in regards to attaining a competitive edge for Al-Noor University. The research has come to a conclusion that the shift towards digital marketing contributes to the better responsiveness of educational institutions to changes in the market and enhances their innovativeness and ability to provide great services for their clients, thus contributing to gaining competitive edge for the Al-Noor University.